2022
DOI: 10.3389/fendo.2022.815703
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Islet Autoantibodies in Children and Adolescents With Type 1 Diabetes Mellitus: A Global Scoping Review

Abstract: Background and PurposePancreatic islet autoantibodies (iAb) are the hallmark of autoimmunity in type 1 diabetes. A more comprehensive understanding of the global iAb prevalence could help reduce avertible morbidity and mortality among children and adolescents and contribute to the understanding in the observed differences in the incidence, prevalence and health outcomes of children and adolescents with type 1 diabetes across and within countries. We present the first scoping review that provides a global synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Type 1 diabetes (T1D) results from the destruction of insulin‐producing pancreatic β ‐cells by auto‐reactive T cells that have escaped central and peripheral immune tolerance 1‐6 . The disease is characterised by a wide heterogeneity especially in terms of age at onset, insulin secretory capacity (mirrored by the residual β ‐cell function) and complication/progression rates.…”
Section: Palmer Et Al 20049 Sørensen Et Al 201310 Greenbaum Et Al 201...mentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 diabetes (T1D) results from the destruction of insulin‐producing pancreatic β ‐cells by auto‐reactive T cells that have escaped central and peripheral immune tolerance 1‐6 . The disease is characterised by a wide heterogeneity especially in terms of age at onset, insulin secretory capacity (mirrored by the residual β ‐cell function) and complication/progression rates.…”
Section: Palmer Et Al 20049 Sørensen Et Al 201310 Greenbaum Et Al 201...mentioning
confidence: 99%
“…diabetes endotypes, immunogene therapy, PD-L1-expressing HSPCs, type 1 diabetes Type 1 diabetes (T1D) results from the destruction of insulinproducing pancreatic β-cells by auto-reactive T cells that have escaped central and peripheral immune tolerance. [1][2][3][4][5][6] The disease is characterised by a wide heterogeneity especially in terms of age at onset, insulin secretory capacity (mirrored by the residual β-cell function) and complication/progression rates. Such heterogeneity represents a major barrier for both pathogenesis and especially for translational therapeutic efforts, thus prompting a reflection on different T1D patient endotypes for identifying the specific one that may benefit most from novel therapeutics.…”
mentioning
confidence: 99%
“…Type 1 diabetes is characterized by elevated blood glucose levels due to insulin deficiency caused by loss of pancreatic b-cells, and it is a common chronic disease in children and adolescents, along with mental disorders (2,21,22). Studies have shown that T1DM brings great psychological burden to children and adolescents, and greatly increases the risk of mental health problems (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the prevalence of IA is not a universal phenomenon in T1DM, and around one-fourth of T1DM may lack IA [3]. Diabetes is a heterogeneous disease with no pathognomonic genetic and autoimmune markers, and the distinction is based on phenotypic and clinical behavior, and with this premise, routine IA testing is also not recommended [3]. Autoimmunity can be implicated in the pathogenesis of disease by demonstrating specific circulating autoantibodies, histopathological evidence of autoimmune inflammation, and the beneficial effects of immunomodulatory therapy [4].…”
mentioning
confidence: 99%
“…IA was found in 11.6% of patients with clinically diagnosed T2DM [2]. Similarly, the prevalence of IA is not a universal phenomenon in T1DM, and around one-fourth of T1DM may lack IA [3]. Diabetes is a heterogeneous disease with no pathognomonic genetic and autoimmune markers, and the distinction is based on phenotypic and clinical behavior, and with this premise, routine IA testing is also not recommended [3].…”
mentioning
confidence: 99%